THE ORGANIZATION AS A SUBJECT OF STUDY: THE ORGANIZATION AS A SUBJECT OF STUDY - Nikolova, Yana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article examines the main internal mechanisms that build social organizations and nuances the differences between the structures in the state apparatus and the corporations.